Thermoelastic interactions in a transversely isotropic cylinder subjected to ramp type increase in boundary temperature and load - Mukhopadhyay S.; Mukherjee R.N. (My University, 2025)
Thermoelastic interactions in an infinitely long transversely isotropic cylinder are investigated. The lateral surface of the cylinder is subjected to (i) ramp-type increase in temperature and zero stress and (ii) ramp-type increase in load and zero temperature change. The problem is studied using coupled dynamical theory of thermoelasticity and the two generalized theories of thermoelasticity, namely, LS theory and GL theory. The analytical solution is obtained by direct approach without the use of potential functions. Laplace transform procedure is employed to obtain the solution in the Laplace-transform domain. The inversion process is carried out by using numerical method based on Fourier series expansions. Numerical results of temperature and stresses are computed and depicted in the form of graphical plots. Comparison is made with the results obtained for two different boundary conditions in the contexts of three different theories.